Digital Transformation of Community Fisheries Business through Business Management Information System: Case Study in Meranti Paham Village - Harun, Ali; Daulay, Armainuddin; Gusman, Boy; Sari, Rida Kurnia; Elida, Syofia; Sumitro, Sumitro (Lembaga Riset Mutiara Akbar, 2025)
This study aims to evaluate the implementation and impact of the use of Business Management Information System (BIMS) on operational efficiency and increasing fishermen's income in Meranti Paham Village, Labuhanbatu Regency, North Sumatra. The background of this study is based on the low efficiency of traditional fisheries businesses due to the absence of a structured information recording and management system. With a qualitative approach through case studies, data were obtained through in-depth interviews, participatory observations, and documentation of 15 fishermen, community leaders, and representatives of the Fisheries Service. The results of the study indicate that the implementation of BIMS, which includes recording catches, distribution, and financial reports, can improve the efficiency of fuel use, operational planning, and cost control. Economically, the use of BIMS increases fishermen's income by 20–30% and strengthens their bargaining power in the market. The success of the implementation is influenced by the support of cooperatives, the role of local leadership, and family involvement. However, obstacles such as limited digital infrastructure, low technological literacy, and concerns about data privacy are still challenges. This study recommends strengthening ongoing training, increasing access to technology, and policy support so that BIMS can be adopted more widely in the community fisheries sector.